2012
DOI: 10.1128/iai.05887-11
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum 19-Kilodalton Merozoite Surface Protein 1 (MSP1)-Specific Antibodies That Interfere with Parasite GrowthIn VitroCan Inhibit MSP1 Processing, Merozoite Invasion, and Intracellular Parasite Development

Abstract: cMerozoite surface protein 1 (MSP1) is a target for malaria vaccine development. Antibodies to the 19-kDa carboxy-terminal region referred to as MSP1 19 inhibit erythrocyte invasion and parasite growth, with some MSP1-specific antibodies shown to inhibit the proteolytic processing of MSP1 that occurs at invasion. We investigated a series of antibodies purified from rabbits immunized with MSP1 19 and AMA1 recombinant proteins for their ability to inhibit parasite growth, initially looking at MSP1 processing. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 39 publications
5
35
1
4
Order By: Relevance
“…6). This is in contrast to previous reports showing that antibodies to MSP1-19 can be internalized and result in delayed or inhibited intraerythrocytic parasite development in some cases (70).…”
Section: Fig 3 Gpi-anchored Msp2 Is Carried Into Invaded Rbcs and Rapcontrasting
confidence: 99%
See 4 more Smart Citations
“…6). This is in contrast to previous reports showing that antibodies to MSP1-19 can be internalized and result in delayed or inhibited intraerythrocytic parasite development in some cases (70).…”
Section: Fig 3 Gpi-anchored Msp2 Is Carried Into Invaded Rbcs and Rapcontrasting
confidence: 99%
“…The ability of antibodies to be carried into invaded RBCs was observed previously for MSP1-19, with internalization of noninhibitory monoclonal antibodies (24,25) as well as inhibitory polyclonal rabbit antibodies, which can result in a specific growth delay (70). Other studies have reported that antibodies to MSP1 are able to disrupt intraerythrocytic development as well as inhibit invasion (81), a process that may be due to the internalization of antibodies during invasion.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations